An Analysis of Slip Incidence for Ankle Angle and Muscle Fatigue During Walking Activities - Ali, Sharifah Aznee Syed; Kamat, Seri Rahayu; Ito, Momoyo (Teknomekanik, 2021)
Human walking speed exposes the higher potential to slip accident especially walking on the oily surface. Prolong walking during working will develop fatigue to the leg and certain body part. In a certain industry, there was a need that worker had to walk and standing in prolong before reaching their break. The aim of this study was to analyze the ankle angle and the muscle fatigue during walking and influence in slip incident. The study involves twelve health participants aged from 23 to 57 years old with a mean of BMI was 27.82 ± 4.01 kg/m2. The procedure will be explained the detail when the participant agreed. Vicon motion capture was used to record movements and the Electromyography (EMG) was used to record muscle fatigue activity. The finding shows that the slip occurred frequently for overweight and obese participants. The female participant experience slips more than a male participant. The range of ankle angle during slip was from 97.2 ± 6.7° for male participants and 112.5 ± 12.7° for female participants. The muscle Soleus and Tibialis were producing high muscles fatigue during slip occurrence. The results of the study show that muscle fatigue was significant with the occurrence of slipping during walking speed. Other findings presented that overweight and obese participants' significant slip occurred when walking on oily surfaces. Both aged groups represent the slip occurrence, there was no significant factor of aged during slip occurrence.